The Arctic Rivers Project: Using an Equitable Co‐Production Framework for Integrating Meaningful Community Engagement and Science to Understand Climate Impacts - Nicole Herman‐Mercer; Alestine Andre; Victoria Buschman; Dylan Blaskey; Cassandra Brooks; Yifan Cheng; Evelynn Combs; Karen Cozzetto; Serena Fitka; Joshua Koch; Aine Lawlor; Elizabeth Moses; et al. (Community Science, 2023)
Abstract As the Arctic and its rivers continue to warm, a better understanding of the possible future impacts on people would benefit from close partnership with Indigenous communities and scientists from diverse fields of study. We present efforts by the Arctic Rivers Project to conduct community‐engaged research to increase collective understanding of the historical and potential future impacts of climate change on rivers, fish, and Indigenous communities. Working in central to northern Alaska and the Yukon Territory in Canada, the project seeks to engage with Indigenous communities in ethical and equitable ways to produces science that is useful, useable, and used that may serve as an example for future research efforts. Toward this goal, we formed an Indigenous Advisory Council and together developed project‐specific knowledge co‐production protocols. This paper provides a novel model of design and implementation to co‐produce knowledge with communities across a large study domain.